1993
DOI: 10.1093/bja/70.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of the Obese Patient

Abstract: Obesity has become a worldwide epidemic in both industrial and developing nations. The precursors of obesity include gender, genetics, environment, ethnicity, education and socioeconomic status. Obesity related medical conditions are reversible following surgical weight loss. Laparoscopy is the preferred operative approach since it is associated with less postoperative pain, earlier recovery and reduced risk of postoperative pulmonary complications. Surgical options currently include either strictly restrictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
23

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(133 citation statements)
references
References 92 publications
0
110
0
23
Order By: Relevance
“…These clinical results support previous laboratory studies documenting increased fibrinogen concentration in MO subjects 2,7 and the clinical appreciation of the increased risks of thromboembolism in this group. 1 The lack of any difference in the percentage fibrinolysis with the TEG in the MO group may suggest an imbalance in the face of the accelerated clot formation. These clinical data support recent laboratory evidence of increased PAI-1 activity and decreased fibfinolysis in obese subjects, 2,4 although in our study, global fibrinolytic activity was not decreased per se compared with lean control patients.…”
Section: Discussionmentioning
confidence: 98%
“…These clinical results support previous laboratory studies documenting increased fibrinogen concentration in MO subjects 2,7 and the clinical appreciation of the increased risks of thromboembolism in this group. 1 The lack of any difference in the percentage fibrinolysis with the TEG in the MO group may suggest an imbalance in the face of the accelerated clot formation. These clinical data support recent laboratory evidence of increased PAI-1 activity and decreased fibfinolysis in obese subjects, 2,4 although in our study, global fibrinolytic activity was not decreased per se compared with lean control patients.…”
Section: Discussionmentioning
confidence: 98%
“…This was explained by the supine position and the paralysis of abdominal muscles in those morbidly obese patients [22]. By comparing mean values of end tidal CO 2 in groups I and II we found that no change in end tidal CO 2 .…”
Section: Resultsmentioning
confidence: 79%
“…However, the perioperative mortality rate reported in morbidly obese patients is high (6.6%) as compared to the mortality rate of non-obese patients submitted to GI tract surgeries (2.6%) 9 . These results might be explained by the fact that obesity leads to several pathophysiological problems, including cardiovascular, respiratory, endocrine and metabolic changes which may negatively affect perioperative results 4,6,10 . In addition to these clinical consequences, overweight may lead to several problems requiring anesthesiologists' understanding and skill to be successfully reverted.…”
Section: Alterações Endócrinas Metabólicas Farmacocinéticas E Farmamentioning
confidence: 99%